Kontribusi Pembiayaan yang Diberikan oleh Perbankan Syariah Terhadap Produk Domestik Regional Bruto di Pulau Jawa Dan Sumatera Tahun 2012-2016 - Purwanto Purwanto; Fuad Yanuar Akhmad Rifai (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
As an intermediary division, the role of sharia banking is very important in order to create added value or increase economic production in an area. Sharia banking will not play a role in economic development if it does not channel funds in the midst of under-funded communities. This study aims to analyze how the contribution of financing from sharia banking in Sumatra and Java in increasing GDRP. In order to analyze this study, we used a panel data regression analysis using Eviews 7 software. The result of this study is the financing provided by sharia banks in Sumatera and Java in 2012-2016 contribute significantly to the increase of GDRP. The contribution given is 50.11 percent. This means that the financing provided by sharia banks contributes 50.11 percent to the increase of GDRP in Sumatra and Java.